Evaluating cytotoxic and genotoxic effects of microcystin using Saccharomyces cerevisiæ as eukaryotic cell model - Barreiros, Sara (2017)
Microcystins (MC) are one of the most common hepatoxins, produced by cyanobacteria. These toxins are cyclic peptides that have a high affinity for the Serine / Threonine (PPs) protein phosphatases family, namely PP1 / PP2A, acting as their inhibitors. MCs also induce oxidative stress in cells through the production of reactive oxygen species (ROS). Both effects have been associated to cytotoxic and genotoxic effects of MC in animal cells [1]. The effects of MCs on cells of higher eukaryotic organisms, such as animals and plants, have been extensively studied. However, a complete characterization of the effects of these toxins has not yet been achieved [1]. In this study the cytotoxic and genotoxic effects of MC on a eukaryotic cell model (the yeast Saccharomyces cerevisiæ) were evaluated. The cytotoxic effects were assessed using an MTT assay and the genotoxic effects evaluated using the comet assay and the expression levels of genes involved in DNA repair systems obtained by Real-Time PCR (RT-qPCR). The results obtained will be discussed.